RANCANG BANGUN SISTEM LIFE TIME PROSES PENYINARAN PADA ALAT TERAPI INFRA MERAH - Aldrin Waoma; Yulizham Yulizham (JURNAL MUTIARA ELEKTROMEDIK, 2019)
The current Infrared therapy device is still operated manually and there is no data on the length of the system's irradiation time. Lack of manufacturer's Infrared devices when used by physiotherapists do not know the exact time produced by Infrared light. This can pose a risk of neglect in monitoring the length of time the patient is exposed to the radiation. To overcome these problems, an infrared therapy device is designed which is equipped with a timer / timer system based on the ATMega8535 microcontroller. With this timing / timer system, we can find out the age of the infrared lamp (life time) according to the amount of usage needed so that the lamp replacement can be estimated according to the total usage of the IR lamp. With this system, on the other hand it is very useful for physiotherapy operators where physiotherapy operators can find out the time of use / irradiation of Infrared therapy devices to patients. So it can help patients who need infrared therapy without fear of side effects due to time that is not in accordance with the required therapy process.